2012
DOI: 10.1127/0003-5548/2012/0173
|View full text |Cite
|
Sign up to set email alerts
|

Variant in the FTO gene and biomarkers related to health in mature Slovak women

Abstract: The purpose of this study was to investigate whether variant (rs178 17449, G/T) in the first intron of the fat mass and obesity-associated gene (FTO) was related to different obesity parameters and blood pressure in mature women from Slovakia. A total of 419 Slovak women (241 premenopausal and 178 postmenopausal) ranging in age from 39 to 65 years were recruited from different parts of Slovakia. The subgroups were categorized based on the WHO (1996) criteria. All participants gave written informed consent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was found that bone mineral density also varies depending on race and ethnicity. Interestingly, Benčová et al 22 found higher BMI in women Slovak aged 60-69 years compared to women from Italy at the same age. Statistically significant differences were found in age, body height, body weight, hip circumference, and BMI between groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that bone mineral density also varies depending on race and ethnicity. Interestingly, Benčová et al 22 found higher BMI in women Slovak aged 60-69 years compared to women from Italy at the same age. Statistically significant differences were found in age, body height, body weight, hip circumference, and BMI between groups.…”
Section: Discussionmentioning
confidence: 97%
“…The mean age was significantly higher in women with osteoporosis, but the other differing parameters were lower in comparison with control (Table 1). Interestingly, Benčová et al 22 found higher BMI in women Slovak aged 60-69 years compared to women from Italy at the same age. The average BMI in the control group of the majority of the population is partly consistent with the results of Piedra et al 23 in the Caucasian population.…”
Section: Discussionmentioning
confidence: 97%
“…Details of the studies have been published elsewhere (Luptáková et al 2012a;Luptáková et al 2012b;Benčová et al 2012;Lupták-ová et al 2013). Women were recruited from different localities in the western, southern and middle parts of Slovakia, via an invitation letter regarding the study which was circulated and distributed prior to data collection with the help of local medical doctors and/or nurses.…”
Section: Methodsmentioning
confidence: 99%